2017
DOI: 10.1002/hed.24934
|View full text |Cite
|
Sign up to set email alerts
|

Outpatient versus inpatient thyroidectomy: A systematic review and meta‐analysis

Abstract: The results suggest outpatient thyroidectomy may be as safe as inpatient thyroidectomy in appropriately selected patients. The results are limited by high risk of bias. Well-designed prospective studies are necessary to further assess the safety of outpatient thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
61
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 40 publications
6
61
0
3
Order By: Relevance
“…15 Another study at the Fallon Clinic (Worcester, MA) similarly reported low complication rates and modest savings from same-day parotidectomies. 11 The studies on outpatient thyroidectomies are more extensive and report similar results in which the outpatient cohort have significantly reduced rates of complications. [9][10][11] Our findings, therefore, support the argument that outpatient parotidectomies are at least as safe as inpatient parotidectomies in selected patients.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…15 Another study at the Fallon Clinic (Worcester, MA) similarly reported low complication rates and modest savings from same-day parotidectomies. 11 The studies on outpatient thyroidectomies are more extensive and report similar results in which the outpatient cohort have significantly reduced rates of complications. [9][10][11] Our findings, therefore, support the argument that outpatient parotidectomies are at least as safe as inpatient parotidectomies in selected patients.…”
Section: Discussionmentioning
confidence: 91%
“…11 The studies on outpatient thyroidectomies are more extensive and report similar results in which the outpatient cohort have significantly reduced rates of complications. [9][10][11] Our findings, therefore, support the argument that outpatient parotidectomies are at least as safe as inpatient parotidectomies in selected patients. Although there are potential liabilities to discharging patients the same day as their operation, there are also risks associated with longer hospital stays, as may be evidenced by this study.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations